Histomorphological and Histochemical Study of Adrenal Gland in Adult Male of Guinea Pigs (Cavia porcellus): Abbas. L. Batah1 and Shakir. M. Mirhish2 - Batah, Abbas. L. (The Iraqi Journal of Veterinary Medicine, 2019)
The present study was carried on twenty adult males of Guinea pigs to evaluate the histomorphological and histochemical features of adrenal gland. Morphologically, Guinea pigs had a couple adrenal glands brown in color were located craniomedially attached to each cranial pole of kidney, the right adrenal gland had pyramidal shape, while the left had elongated shape. The statistical results showed that there is significant difference between the right and left adrenal gland in the weight, length, thickness, width and volume. The histological and histochemical results showed that adrenal gland was composed of cortex and medulla. The cortex was consisted of three zones. The zona glomerulosa was consisted of columnar or cuboidal cells arranged in groups as glomeruli, the zona fasciculata and reticularis were composed mainly of polygonal cells arranged in regular and irregular cords.The medulla region was composed of ovoid group of cells (chromaffine cells) that arranged in irregular cords separated by blood sinusoid and surrounded by central vein, contained two types of cells, the first cell was columnar in shape and brownish in color representing the epinephrine secreting cell, the second cell was polygonal in shape and light brownish in color with spherical nucleus representing the Norepinephrine secreting cell when fixed in chromate salts. All parts of adrenal gland exhibited strong to moderate reaction for Periodic Acid Schiff stain. The statistical results showed that there is significant difference between the right and left adrenal gland in the thickness of capsule, zona glomerulusa, zona fasciculata, zona reticularis and medulla region.